Understanding and Addressing Barriers to Indigenous Learners in Business and Accounting Studies - Andrews, Cyril Robert (Graduate Studies, 2023)
This research addresses a significant gap in understanding the barriers Indigenous peoples face as they pursue business and accounting disciplines at the post-secondary level. Using structured interviews and content analysis, the study explored barriers and means the learners used and opined to remove or reduce those barriers. In addition, the research offers policy recommendations, including but not limited to the accounting profession, to address these challenges. The research also examines Indigenous peoples’ attitudes toward the accounting and business profession. This practical approach, with application to the accounting profession, bridges the practitioner-scholar gap noted in extant research. The findings suggest that the challenges are complex and interconnected and are deeply socialized in the fabric of Canada through societal biases and structural impediments within institutions that directly result from government policy, reserves, and residential schools. The research highlights issues not previously identified in the literature, including lateral violence and anti-business stigma within the Indigenous community as well as identifying an ontological reductionist fallacy of grouping dissimilar peoples together and forming policy as programs as though these groups were homogenous. Moreover, the colonial legacy, legislative and regulatory environments create a unique context for the study. It concludes that the nature of the problem may best be understood as a “wicked problem” and that collaborative approaches are likely the most suited to addressing the identified barriers. A conceptual co-evolutionary framework is proposed to relate the various barriers, structural impediments, and resulting barriers to business education specifically but also to post-secondary education generally.